Lipopolysaccharide-induced functional and structural injury of the mitochondria in the nigrostriatal pathway. (January 2017) - Hunter, Randy; Ojha, Uttam; Bhurtel, Sunil; Bing, Guoying; Choi, Dong-Young
Highlights: Striatal injection of LPS caused dopaminergic neurodegeneration. Functional deficit was detected in the mitochondria. In the mitochondria, structural damage and oxidative modification were observed. Mitochondrial injury is related to the neuronal loss. Abstract: Accumulating evidence suggests that chronic inflammation plays a role in the progressive dopaminergic neurodegeneration that occurs in Parkinson's disease. It has been hypothesized that inflammation mediates neuronal damage via exacerbation of a vicious cycle of oxidative stress and mitochondrial dysfunction. The bacterial endotoxin, lipopolysaccharide (LPS), induces microglial activation and inflammation driven dopaminergic neurodegeneration. In order to test the hypothesis that LPS-induced inflammatory response might damage mitochondrial structure and function leading to nigral dopaminergic neuron loss, we injected LPS or saline into the striatum of rats. Here, we found that intrastriatal LPS induced deficit in mitochondrial respiration, damage to mitochondrial cristae, mitochondrial oxidation and nitration. Finally, we found significant loss of dopaminergic neurons in the substantia nigra one week after LPS injection. This study indicates that LPS-induced dopaminergic neurodegeneration might be exerted by mitochondrial injury.